Late diagnosis of Fabry Disease in hemodialysis patient - S. Fomina; O. Ovska (Ukrainian Journal of Nephrology and Dialysis, 2019)
The Fabry Disease in young white man with End Stage Renal Disease was reported. Diagnosis was detected at stage of hemodialysis treatment despite sings which admitted as clinical criteria were found at childhood but did not identify during 20 years due limited awareness of medical community about lysosomal disorders.